2019
DOI: 10.3390/cancers11081201
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Receptor B signaling Reduces Breast Cancer Cell Aggressiveness: Role of Cyclin-D1/Cdk4 Mediating Paxillin Phosphorylation

Abstract: Progesterone-Receptor (PR) positivity is related with an enhanced response to breast cancer therapy, conversely cyclin D1 (CD1) is a retained marker of poor outcome. Herein, we demonstrate that hydroxyprogesterone (OHPg) through progesterone receptor B (PR-B) reduces breast cancer cell aggressiveness, by targeting the cytoplasmic CD1. Specifically, OHPg diminishes CD1 expression by a transcriptional regulation due to the recruitment of PR-B at a canonical half-PRE site of the CD1 promoter, together with HDAC1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 61 publications
1
18
0
Order By: Relevance
“…We also observed a decrease in phospho-paxillin and Rac1 in miR-141 overexpressing cells compared to controls. Elevated paxillin phosphorylation is common in cancer tissues and is associated with tumorigenesis, EMT, and metastasis 15,16,50 . Paxillin interacts with numerous molecules, controlling the Rho family of GTPases, that are crucial regulators of adhesion dynamics 16,51 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also observed a decrease in phospho-paxillin and Rac1 in miR-141 overexpressing cells compared to controls. Elevated paxillin phosphorylation is common in cancer tissues and is associated with tumorigenesis, EMT, and metastasis 15,16,50 . Paxillin interacts with numerous molecules, controlling the Rho family of GTPases, that are crucial regulators of adhesion dynamics 16,51 .…”
Section: Discussionmentioning
confidence: 99%
“…Elevated paxillin phosphorylation is common in cancer tissues and is associated with tumorigenesis, EMT, and metastasis 15,16,50 . Paxillin interacts with numerous molecules, controlling the Rho family of GTPases, that are crucial regulators of adhesion dynamics 16,51 . Rac1 GTPase is required for cell migration and its hyperactivation results in cancer invasiveness and progression 52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Pxn contains many phosphorylation sites, and it was demonstrated that Pxn acts as a substrate for the Cyclin D1/CDK4 complex [ 86 ]. We recently reported that low levels of Pxn phosphorylation at Ser 83, resulting to the reduced Cyclin D1/CDK4 functional interaction, led to the inhibition of mediators of membrane ruffles and actin rearrangements such as Rac1 and its effector Pak, as evidenced by the reduction of pSer144-Pak1 levels [ 88 ] (see Figure 2 ).…”
Section: Membrane Associated and Cytoplasmatic Cyclin D1: Linking mentioning
confidence: 99%
“…Recent findings in cancer progression investigate new possible molecular mechanisms regulating invasion, epithelial mesenchymal transition (EMT) [76,77], and the possible link with autophagy. It is reported that (synaptojanin 2 binding protein) SYNJ2BP, crucially involved in the pathogenesis of metastatic breast tumors, is responsible of the degradation of PTEN through the lysosomes; particularly, SYNJ2BP stimulates the recruitment of PTEN at autophagy-lysosomes, the autophagosome cargo (p62) expression, and LC3-I to LC3-II conversion.…”
Section: Regulation Of Emt and Invasion Through Autophagy By Ptenmentioning
confidence: 99%